Anode ink formulation for a fully printed flexible fuel cell stack. (20th April 2020) - Hakola, Liisa; Parra Puerto, Andres; Vaari, Anu; Maaninen, Tiina; Kucernak, Anthony; Viik, Saara; Smolander, Maria
Abstract: In fuel cells the underlying reactions take place at the catalyst layers composed of materials favoring the desired electrochemical reactions. This paper introduces a formulation process for a catalyst inkjet ink used as an anode for a fully printed flexible fuel cell stack. The optimal ink formulation was 2.5 wt% of carbon–platinum–ruthenium mixture with 0.5% Nafion concentration in a diacetone alcohol solvent vehicle. The best jetting performance was achieved when 1 wt% binder was included in the ink formulation. Anodes with resistivity of approximately 0.1 Ω cm were inkjet printed, which is close to the commercial anode resistivity of 0.05 Ω cm. The anodes were used in fuel cell stacks that were prepared by utilizing only printing methods. The best five-cell-air-breathing stack showed an open circuit potential under H2 /air conditions of 3.4 V. The peak power of this stack was 120 µ W cm −2 at 1.75 V, with a resistance obtained from potentiostatic impedance analysis of 295 Ohm cm 2 . The printed electrodes showed a performance suitable for low-performance solutions, such as powering single-use sensors.